2021
DOI: 10.1186/s40104-021-00557-3
|View full text |Cite
|
Sign up to set email alerts
|

Maternal antibiotic treatment affects offspring gastric sensing for umami taste and ghrelin regulation in the pig

Abstract: Background Scarce is knowledge on the process regulating the development of acid secretion, orexigenic signaling, and chemosensing in the stomach of young pigs. Changes of early microbial encounters by suckling pigs can interact with the gut maturation, by the induction of different molecular signaling. Our goal was to assess if the age of offspring and the maternal environment, influenced by sow antibiotic treatment peripartum, could affect gastric morphology and the expression of genes involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Importantly, we studied gene transcript level and not protein expression (or activity where appropriate) at the gastric level, which constitutes a limitation of our study. A recent study in older piglets described an increase in ghrl but no variation of goat or pcsk1/3 expressions between PND 14 and 42 ( Trevisi et al, 2021 ). However, timepoints at younger ages as well as corresponding plasma ghrelin levels like in our study were not reported.…”
Section: Discussionmentioning
confidence: 91%
“…Importantly, we studied gene transcript level and not protein expression (or activity where appropriate) at the gastric level, which constitutes a limitation of our study. A recent study in older piglets described an increase in ghrl but no variation of goat or pcsk1/3 expressions between PND 14 and 42 ( Trevisi et al, 2021 ). However, timepoints at younger ages as well as corresponding plasma ghrelin levels like in our study were not reported.…”
Section: Discussionmentioning
confidence: 91%
“…One study suggests modulation of the olfactory receptor OR51E1 by the gut microbiome and factors that affect the complexity of the microbiota [ 91 ]. For taste receptors so far, it has been shown that maternal antibiotic administration leads to an upregulation of the TAS1R1 gene for the umami taste receptor TAS1TR in the stomach of suckling piglets [ 92 ]. However, there is no evidence that increased expression of TAS1R1 could affect piglet appetite.…”
Section: Species-specific Considerationsmentioning
confidence: 99%
“…Pig production faces problems similar to those of rabbit production related to dysbiosis during the post-weaning period, which was traditionally controlled with the use of antibiotic-medicated feed and supplementation with high levels of minerals (particularly copper and zinc) [ 58 ]. The ban on (or limited use of) antibiotics has led to the need for feeding strategies in the post-weaning period that can re-establish the gut eubiosis lost at weaning, aimed at restoring the Lactobacillus count, promoting the growth of beneficial bacteria that boost the mucosal immune system and lowering the proliferation of pathogenic bacteria [ 83 ]. The pig farming sector already has some experience in using seaweed to improve the health and performance of piglets while avoiding the use of in-feed antibiotics (for a review, see [ 58 , 61 , 63 ]).…”
Section: Seaweed and Gut Healthmentioning
confidence: 99%